Strategi Manajemen Operasional Bisnis dengan Metode Lean Manufacturing untuk Meningkatkan Pendapatan - Dinda Tiara; Novera Martilova (Universitas 45 Surabaya, 2024)
This research aims to minimise waste by using the Lean Manufacturing method business operational strategy at CV Cassiavera Merapi, owned by Mr Daswir, in Jorong Lasi Tuo, Canduang District, Agam Regency. This research uses qualitative methods through interviews, documentation, and observation with the owner and employees. The results showed that the application of Lean Manufacturing with Kaizen and Just In Time principles reduced operational waste. Kaizen principles include 3M (eliminating wasteful activities, bringing order to the production process, and reducing employee overload), the 5S concept (separating and organising goods, cleaning, and maintenance), and the PDCA cycle (Plan, Do, Check, Action) with 5W+1H. Just In Time improves productivity and timeliness. The obstacle faced is the lack of special specifications for employees, so the solution is that company owners must be more selective in employee selection.